Analisis Bibliometrik Green Human Resource Management (GRHM) terhadap Kinerja Lingkungan di Perusahaan - Yayah Sutisnawati (Universitas Medan Area, 2023)
Green Human Resource Management (GHRM) is a topic of human resource empowerment that leads to sus-tainable systems and the environment. This research was conducted with the aim of identifying the relation-ship between research on GHRM and sustainable environmental performance practices in a company as well as to find new information for further research. To achieve this goal, a bibliometric analysis method was used by collecting 838 research articles that had been published on Google Scholar and were in line with the research object. Bibliometric and overlay analysis carried out by observing the network formed from the to-pics of GHRM and environmental performance shows diverse relationships with various scientific disciplines, especially those related to human resources and companies. The link between GHRM and environmental performance began at the beginning of 2020. In the 3 years since the GHRM concept was presented, there has been an increase of 43.27% in the number of articles examining this topic. This shows that the sustainable concept with a green theme which symbolizes the environment has been implemented by various sectors by involving human resources in its implementation.